Applying Impromptu Speech Technique to Improve Students’ Speaking Ability at the Fourth Semester Students of STIBA Persada - Barruansyah, Rauf Tetuko (J-SHMIC : Journal of English for Academic, 2018)
Based on the writer’s preliminary study, it was found that the speaking ability of the students were still low. Some of students were not able to pronounce well, were not able to express their ideas, and were afraid of making mistakes when they were speaking. All of those problems were caused by several factors, one of them was the way of teaching was not appropriate for the students. In this research, the writer applied Impromptu Speech technique which has been proven can improve students’ speaking ability, it is one teaching technique that is very useful for teaching speaking. This technique enables students to develop their capability to think on their feet, organize ideas quickly, and speak informatively and confidently about variety of topics. The subject of this research was the fourth semester students of Sekolah Tinggi Ilmu Bahasa Asing (STIBA) PersadaBunda, and the object was the effect of applying Impromptu Speech technique. The writer used simple sampling to take the sample. The writer used Non Equivalent control group design that used one group as the experimental class and one group as control class. The writer used Independent Sample t-test to analyze the data. Based on the data analysis, Consideration Sig (2tailed) t0= 0.000 is lower than Sig (2 tailed) ttable= 0.005, it means Ha was accepted and H0 is rejected. So, it can be concluded that there is a significant effect of applying Impromptu Speech technique to improve students’ speaking ability at the fourth semester students of STIBA Persada Bunda Pekanbaru.